Electrical Conductance of Acetycholine Perchlorate in Tert-Butanol-Water Mixtures At 25ºC - Nasr. H. El-Hammamy,; Taher s. Kassem,; Aida. I. Kawana, (International Journal of Pharma and Bio Sciences, 2010)
The conductance of acetylcholine perchlorate was measured in tert butanol- water mixtures covering a range of dielectric constant 37<D<68.25 at 25°C. The data was analyzed using the Fuoss-Onsager conductance theory to get Λâ—¦, KA and a°. The equivalent conductance at infinite dilution, for acetycholine perchlorate decrease with the decrease of the dielectric constant of the medium.The ion parameter a°( solvation) for the perchlorate decreases with decrease of the dielectric constant. The plot of log KA vs 1/D was not linear indicating that solvent separated ion pairs in this system is characterized by formation of hydrogen bonding.